2015
DOI: 10.7740/kjcs.2015.60.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect, Antioxidant and Tyrosinase Inhibitory Activity of the Extract from Different Parts of Phytolacca americana L.

Abstract: This study was conducted to clarify the antimicrobial effect, antioxidant and tyrosinase inhibitory activities of the biological composition having the Phytolacca americana, and to enhance the natural materials utilization of foods and cosmetics. The antimicrobial activities of the different parts of P. americana were evaluated using the agar diffusion test. The antimicrobial activity of P. americana was relatively high in Malassezia furfur known as a skin fungi and Vibrio parahaemolyticus compared to Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…However, to best of our knowledge no studies have investigated the phenolic and flavonoid contents for the P. dioica seeds. It is important to highlight that the total phenolic and flavonoid contents reported in this study are appreciably higher than the previous studies 29 , 30 .…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…However, to best of our knowledge no studies have investigated the phenolic and flavonoid contents for the P. dioica seeds. It is important to highlight that the total phenolic and flavonoid contents reported in this study are appreciably higher than the previous studies 29 , 30 .…”
Section: Resultscontrasting
confidence: 84%
“…The bioassays experiments revealed antioxidant activity of the EAE and its constituent (compound 1 ) to be remarkably pronounced with respect to previous studies performed on Phytolacca americana 29 , 30 . Since, no data has been reported in the literature about the antioxidant activity of P. dioica seeds extracts.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…These plant species have been used both traditionally and in modern times as herbal medicines [ 1 ]. The chemical constituents of the species in this family have shown a number of bioactive activities including antibacterial [ 2 , 3 ], antifungal [ 4 , 5 , 6 , 7 , 8 , 9 ], antimalarial [ 10 , 11 ], molluscicidal properties [ 12 , 13 ], and anti-obesity [ 14 ], potential behavioral and pro-oxidant effects [ 15 ], antitumor activities [ 16 ], among others. The compounds responsible for the above activities are reported to be triterpenoid saponins [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plants of P. americana have high concentration of saponin, which has medicinal value but toxic to herbivores (Wang et al, 2008). In medical science, it has been confirmed that the secondary metabolites in P. americana have antibacterial, antioxidant and anti-malignant cell proliferation effects (Patra et al, 2014;Boo et al, 2015). At the same time, some studies have shown that the content of secondary metabolites of P. aericana are higher than that of other Phytolacca members (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%